Effects of garlic supplementation on parasitic infestation, live weight, and hematological parameters in Black Bengal goat - Hasan, Mir Md. Iqbal; Begum, Shahana; Islam, Saiful; Rahman, Md. Mahfujur; Belal, Shah Ahmed; Hossain, Md. Anwar; Akanda, Md. Rashedunnabi; Pal, Nebash Chandra; Howlader, Md. Matiar Rahman (Journal of Advanced Veterinary and Animal Research, 2015)
This study was conducted to determine the effects of garlic on egg per gram (EPG) count of feces for gastrointestinal parasites, live weight, and hematological parameters in Black Bengal goat. A total of 18 dry does of 18-22 months of age were divided into 3 groups as T0, T1 and T2; where, each group comprised of 6 goats. The goats of T0 were feed with normal feeds, whereas the goats of T1 and T2 were fed with normal feeds plus 25 mL and 50 mL of 10% water solution of garlic twice per day, respectively for 60 days. The EPG count was performed by McMaster counting chamber, and live weight was measured by digital electric balance. EPG count for gastrointestinal parasites was found significantly lower in the treatment groups as compared to T0. Weight gain was recorded significantly higher in the treatment groups. The hematological parameters like total leucocyte count (TLC), erythrocyte sedimentation rate (ESR), packed cell volume (PCV), hemoglobin (Hb) and total erythrocyte count (TEC) showed significant changes in the treatment groups. The study suggests that 10% water solution of garlic is a useful supplementation to decrease EPG count, body weight gain; thus, the 10% aqueous garlic solution can improve the general health condition of goat. http://dx.doi.org/10.5455/javar.2015.b102